Arara-azul-grande (Psittaciformes, Aves): informações genéticas para a conservação e o manejo em cativeiro - Lima, Fernanda Ribeiro (Universidade Federal de São Carlos, 2014)
Microsatellites loci can provide valuable information about kinship, diversity estimation and population origin of individuals. These data are essentials for adoption of conservation measures in-situ and ex-situ for endangered species. In the present study, we achieved genetic data on captive individuals of the specie Anodorhynchus hyacinthinus, hyacinth macaw, regarded in endangered of extinction. We analyzed 10 microsatellite loci and performed the molecular sexing to 50 of hyacinth macaw captive in the zoos of the São Paulo State. We determined the sex of individuals without this information and corrected the erroneous identification of the two other specimens. The genetic diversity for captive specimens hyacinth macaw did not differ significantly of the natural populations. We determine the probable populational origin of 89.9% of the captive specimens by population allocation tests and multilocus genotypes of the natural populations. The largest portion of captive specimens were assigned to the North and Northeast region The largest portion of captive specimens were assigned to the North and Northeast populations region. We established the kinship and genetic similarity among 49 captive specimens, focusing on captive individuals in the same institution. More than 70 % of the pairwise combinations among the hyacinth macaw specimens resulted in values of kinship to unrelated individuals, with intermediate values of genetic similarity. The combination of the results of this present study allowed the suggestion of the best couples to breeding in each institution, beyond if they enable better visualization of reproductive pairings between all specimens to ensure the genetic diversity and preserve the evolutionary history of the A. hyacinthinus in captivity.
Keywords: Genética; Conservação; Anodorhynchus hyacinthinus; Zoológico; Parentesco; Atribuição populacional; CIENCIAS BIOLOGICAS::GENETICA